Value of virtual reality integrated with multilevel team-based pedagogy in standardized residency training: a randomized controlled study with longitudinal follow-up in anesthesiology - Chen, Si; Wang, Chuanguang (Frontiers in Medicine, 2026)
BackgroundAchieving both technical and non-technical competencies in anesthesiology residency training remains challenging, highlighting the need for innovative educational strategies.MethodsIn this single-center randomized controlled trial, 120 anesthesiology residents were assigned 1:1 to virtual reality (VR)–integrated team-based pedagogy (VR-TBP, n = 60) or conventional training (n = 60). The intervention combined immersive VR simulations with multilevel team-based teaching, while controls received standard lectures and bedside instruction. Primary outcomes included first-pass tracheal intubation success, intubation time, procedural errors, and ultrasound-guided nerve block performance. Secondary outcomes were Mini Clinical Evaluation Exercise (Mini-CEX), Anesthetists’ Non-Technical Skills (ANTS), theoretical knowledge, self-efficacy, and satisfaction. Long-term endpoints at 6 and 12 months assessed skill retention, independent procedure completion, and adverse events.ResultsBaseline characteristics were comparable. At 12 months, VR-TBP participants achieved higher first-pass intubation success (86.7% vs. 68.3%, p = 0.026), shorter intubation times (60.1 ± 11.0 vs. 66.8 ± 12.6 s, p = 0.006), fewer errors (1.4 ± 0.7 vs. 2.0 ± 0.9, p = 0.007), and greater nerve block success (81.7% vs. 65.0%, p = 0.041). Non-technical outcomes also favored VR-TBP, with higher Mini-CEX (6.7 ± 1.0 vs. 5.9 ± 1.1, p < 0.001) and ANTS scores (11.5 ± 1.6 vs. 9.9 ± 1.7, p < 0.001). Skill retention (88.4% vs. 76.5%, p < 0.001) and independent procedure completion (76.7% vs. 58.3%, p = 0.032) were superior, with comparable adverse event rates.ConclusionIntegrating VR-based simulation with team-based pedagogy significantly enhanced technical and non-technical competencies among anesthesiology residents, with sustained benefits at 12 months. VR-TBP offers an effective, reproducible model to strengthen residency training.